On the Markov property of strong solutions to sde with generalized coefficients - Zaitseva, L.L. (Інститут математики НАН України, 2005)
We present the complete proof of the Markov property of the strong solution to a multidimensional stochastic differential equation, whose coefficients involve the local time on a hyperplane of the unknown process.